The Informal recycling Sector in Developing Countries : Organizing Waste Pickers to Enhance their Impact - Medina, Martin (World Bank, Washington, DC, 2012)
For the urban poor in developing countries, informal waste recycling is a common way to earn income. There are few reliable estimates of the number of people engaged in waste picking or of its economic and environmental impact. Yet studies suggest that when organized and supported, waste picking can spur grassroots investment by poor people, create jobs, reduce poverty, save municipalities money, improve industrial competitiveness, conserve natural resources, and protect the environment. Three models have been used to organize waste pickers: micro enterprises, cooperatives, and public-private partnerships. These can lead to more efficient recycling and more effective poverty reduction.